Aging Increases Compensatory Saccade Amplitude in the Video Head Impulse Test - Anson, Eric R.; Bigelow, Robin T.; Carey, John P.; Xue, Quan-Li; Studenski, Stephanie; Schubert, Michael C.; Weber, Konrad P.; Agrawal, Yuri (Frontiers in Neurology, 2016)
Objective: Rotational vestibular function declines with age resulting in saccades as a compensatory mechanism to improve impaired gaze stability. Small reductions in rotational vestibulo-ocular reflex (VOR) gain that would be considered clinically normal have been associated with compensatory saccades. We evaluated whether compensatory saccade characteristics varied as a function of age, independent of semicircular canal function as quantified by VOR gain. Methods: Horizontal VOR gain was measured in 243 participants age 27-93 from the Baltimore Longitudinal Study of Aging using video head impulse testing (HIT). Latency and amplitude of the first saccade (either covert – occurring during head impulse, or overt – occurring following head impulse) were measured for head impulses with compensatory saccades (n = 2230 head impulses). The relationship between age and saccade latency, as well as the relationship between age and saccade amplitude, were evaluated using regression analyses adjusting for VOR gain, gender, and race. Results: Older adults (mean age 75.9) made significantly larger compensatory saccades relative to younger adults (mean age 45.0). In analyses adjusted for VOR gain, there was a significant association between age and amplitude of the first compensatory covert saccade (β = 0.015, p = 0.008). In analyses adjusted for VOR gain, there was a significant association between age and amplitude of the first compensatory overt saccade (β = 0.02, p < 0.001). Compensatory saccade latencies did not vary significantly by age. Conclusions: We observed that aging increases the compensatory catch-up saccade amplitude in healthy adults after controlling for VOR gain. Size of compensatory saccades may be useful in addition to VOR gain for characterizing vestibular function in aging adults.